The mystery of high performance – mediation by entrepreneurial orientation and organizational citizenship behavior - Przemysław Zbierowski (Journal of Entrepreneurship, Management and Innovation)
The search for high performance is one of the leading themes in management science with a number of frameworks developed over the decades. The purpose of the paper is to investigate if the effect of high performance organization (HPO) characteristics has a direct effect on actual organizational performance or if the effect is mediated by organizational citizenship behavior (OCB) and entrepreneurial orientation (EO). Previous research states that the framework of HPO characteristics answers the question of ‘what’ high performers do, but does not answer the question of ‘how’ they do it, suggesting a mediating effect. The study attempts to establish which of the pair of OCB and EO (if any) has a stronger mediating effect. The hypotheses were tested using a cross-sectional research design with a random and representative sample of 406 enterprises. The research was carried out using the technique of personal interview (CAPI). Established scales were used to measure high performance indicators, organizational citizenship behavior, entrepreneurial orientation, and organizational performance. The conceptual framework with mediated effects was tested using a structural equations modeling approach. Research results indicate that there is a strong direct positive relationship between high performance indicators and organizational effectiveness. Moreover, there is a strong positive effect of high performance indicators on entrepreneurial orientation and organizational citizenship behavior. However, the effect of those two constructs on organizational effectiveness is rather weak, and, in the case of OCB, negative. That leads to the conclusion that the direct effect of high performance indicators is stronger, although the positive mediation by entrepreneurial orientation is statistically significant. The study contributes to the scientific debate in at least three ways. First, it confirms that high performance characteristics have a strong effect on actual performance. Second, it points to entrepreneurial orientation as a partial mediator in that relationship. Finally, it uncovers the very strong effect of high performance characteristics on organizational citizenship behavior. The research results also allow one to formulate practical recommendations. They mainly consider enhancing OCB, EO, and performance by skillful use of high performance factors. The study is novel in its approach to use OCB and entrepreneurial orientation as mediators in the effect of high performance characteristics on organizational performance, as no such attempts were made in the past.